2022
DOI: 10.1155/2022/4742266
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Status Is Associated with Lower Hemoglobin A1c among Nondiabetes Women in the United States from NHANES 2005–2016

Abstract: Background. It has been verified that the incidence rate of diabetes mellitus (DM) is sharply increased in pregnant female adults. However, the relationship between pregnant status and hemoglobin A1c (HbA1c) in nondiabetes women remains unclear. Methods. We conducted a cross-sectional study of 7762 participants in the National Health and Nutrition Examination Survey (NHANES) 2005–2016. Multivariable linear regression models were performed to evaluate the associations between pregnant status with HbA1c and seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Additionally, various studies reporting the capability of HbA1c in diagnosing GDM are inconclusive or controversial. [9][10][11] A number of studies revealed that concentration of HbA1c is relatively lower during gestation because of the pregnancy-related physiological hydremia, anemia, nutritional deficiencies, and shorter life of red blood cells, which may restrict its importance in diagnosing GDM. [9][10][11] A study by Valadan et al reported that HbA1c cannot substitute OGTT for GDM diagnosis owing to the low sensitivity and specificity i.e.…”
Section: Original Articlementioning
confidence: 99%
“…Additionally, various studies reporting the capability of HbA1c in diagnosing GDM are inconclusive or controversial. [9][10][11] A number of studies revealed that concentration of HbA1c is relatively lower during gestation because of the pregnancy-related physiological hydremia, anemia, nutritional deficiencies, and shorter life of red blood cells, which may restrict its importance in diagnosing GDM. [9][10][11] A study by Valadan et al reported that HbA1c cannot substitute OGTT for GDM diagnosis owing to the low sensitivity and specificity i.e.…”
Section: Original Articlementioning
confidence: 99%